IMPLEMENTASI KEBIJAKAN SOSIAL PEMERINTAH MELALUI PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KOTA PALANGKA RAYA: IMPLEMENTASI KEBIJAKAN SOSIAL PEMERINTAH MELALUI PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KOTA PALANGKA RAYA - Asri (Journal Ilmu Sosial, Politik dan Pemerintahan, 2020)
The No Slum City Program is a government response in dealing with slum problems that exist throughout Indonesia, this program is sourced from the center which will be directly included in the RPJM in areas that are declared slum. but at the implementation stage there are obstacles, especially the commitment of the community that is still lacking in terms of reducing the slums that occur in the community itself. The problem under study is a description of the Implementation of Social Policy through the Kumpak City Program in the City of Palangka Raya. This study uses a causal method supported by primer data in the form of in-depth interviews and observations as well as secondary data in the form of document review. From the results of this research, it was shown that the implementation of the Social Policy through the No-Slum City Program (KOTAKU) in the City of Palangka Raya had not been effective. This is based on the lack of socialization, inconsistency of the implementor, and not maximally utilizing the facilities and infrastructure that have been given and the lack of community commitment to achieve the objectives of the KotaKu Program. It is therefore recommended that the government make the community a commitment to the program, and it is hoped that the socialization should be directly in the community, not through the BKM that has been made because this is not effective if it is seen from the commitment of the community.